Growing Cd₁₋x₋yMnyHgxTe single crystals and their optoelectronic properties - Paranchych, S.Yu.; Paranchych, L.D.; Tanasyuk, Yu.V.; Romanyuk, V.R.; Makogonenko, V.M.; Yurtsenyuk, R.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Single crystals of Cd₁₋x₋yMnyHgxTe:V (х = 0.05; у = 0.03-0.07, NV = 1∙10¹⁹ cm⁻³) have been grown and their electrical and optical properties have been studied. The transmission spectra of the samples with the composition x = 0.05; y = 0.07 were characterized by the minimum in the 3.5-5.5 μm spectral range. In order to understand the nature of it the energy diagram of vanadium levels has been considered. The band gap of the studied solid solutions with different manganese content has been found from the absorption coefficient spectra and compared with those calculated.